PRE-DESIGN PRODUCTION SYSTEM OF ORGANIC KALE (IPOMOEA REPTANS POIR.) AND CATFISH (CLARIAS SP.) BY UTILIZING WATER PHYTOREMEDIATION OF METAL MERCURY (HG) AS A SOURCE OF WATERING - Mukaromah
Pollution of heavy metals can cause a decline in the quality and quantity of agricultural products. The concentration of metals in the soil can be reduced by the planting of hyperaccumulator plants through the phytoremediation. The study is conducted in the experimental garden and greenhouse of the Andalas University, Agriculture Faculty for 35 days. The study aims to analyze the differences in growth of kale plants (Ipomoea reptans Poir) grown on mercury (Hg) contaminated soil at various doses of a mixture of compost and nitrogen fertilizers; analyzed the effectiveness of absorption of metal mercury (Hg) by the kale plants (Ipomoea reptans Poir) on various doses of a mixture of compost and nitrogen fertilizers. The design used was RAL (a complete random design) with 3 treatments, namely KU-A (without adding a mixture of compost and nitrogen fertilizers); KU-B (a mixture of compost 5 tons/ha and nitrogen fertilizer 150 kg/ha); and KU-C (a mixture of compost 10 tons/ha and nitrogen fertilizer 300 kg/ha) with 6 replication. The research data of high growth rates, growth rate of leaf number, root length, root dry weight and canopy were analyzed statistically by one way-ANOVA test with a confidence level of 95% (p < 0.05), if there is a difference then it is analyzed by using the LSD test, while the parameters of root proportions, RAR, RLD, and effectiveness of metal absorption, namely IBR and FT, were analyzed descriptively. The results showed that the treatment of KU-A, KU-B, and KU-C differed in the parameters of plant height growth rate, root length and root dry weight. The KU-A treatment showed greatest value compared to other treatments. The effectiveness of kale plants in the KU-A, KU-B, and KU-C treatment were 99,81%; 99,83%; and 99,82%, and the transfer factor values were 1.19; 1,34; and 1,34. In order to obtain the most effective dose of compost and nitrogen fertilizer mixture o the effectiveness of kale plants is KU-B (a mixture of compost 5 tons/ha and nitrogen fertilizer 150 kg/ha).